2021
DOI: 10.1002/aic.17454
|View full text |Cite
|
Sign up to set email alerts
|

Modeling phase formation on catalyst surfaces: Coke formation and suppression in hydrocarbon environments

Abstract: We develop a simulation toolset employing density functional theory in conjunction with grand canonical Monte Carlo (GCMC) to study coke formation on Fe-based catalysts during propane dehydrogenation (PDH). As expected, pure Fe surfaces develop stable graphitic coke structures and rapidly deactivate. We find that coke formation is markedly less favorable on Fe 3 C and FeS surfaces. Fe-Al alloys display varying degrees of coke resistance, depending on their composition, suggesting that they can be optimized for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
(134 reference statements)
0
2
0
Order By: Relevance
“…In several DFT studies, the correlation between the adsorption energy of a single carbon atom on a metallic surface and the proneness for the formation of coke was observed. In the case of Ni, this was reported for the water‐gas‐shift reaction, [85] the dry reforming of methane, [86,87] and for other transition metals and alloys in PDH [88] . These studies demonstrated that the C‐atom adsorption energy is a descriptor for the formation of coke.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…In several DFT studies, the correlation between the adsorption energy of a single carbon atom on a metallic surface and the proneness for the formation of coke was observed. In the case of Ni, this was reported for the water‐gas‐shift reaction, [85] the dry reforming of methane, [86,87] and for other transition metals and alloys in PDH [88] . These studies demonstrated that the C‐atom adsorption energy is a descriptor for the formation of coke.…”
Section: Resultsmentioning
confidence: 75%
“…In the case of Ni, this was reported for the watergas-shift reaction, [85] the dry reforming of methane, [86,87] and for other transition metals and alloys in PDH. [88] These studies demonstrated that the C-atom adsorption energy is a descriptor for the formation of coke. Here, DFT calculations were carried out to validate the coking ability of different NiGa surfaces.…”
Section: Structural Investigationmentioning
confidence: 98%